Rescuing Banks in Financial Distress: A Case Study of Yes Bank Using The ‎EAGLES Model - Pauldurai , T. Augustus Immanuel; Thangam , Dr. D. Mahila Vasanthi; R, Dr. Sangeetha; Meenakshi, Dr. J. Raja (International Journal of Accounting and Economics Studies, 2025)
Banks play a vital role in economic development. Failure of banks will have a contagion ‎effect on the economy badly, and hence the government is taking all its efforts to prevent bank failure ‎of any sort. One of the new generation private sector banks is Yes Bank, which was started in 2004 ‎and was thought to be doing well until its huge non-performing assets came to light during the financial ‎year 2020. In this paper, the bank’s performance after the restructuring process taken by the State ‎Bank of India has been analyzed to understand the turnaround strategy, using the EAGLES model ‎of performance analysis. It is exploratory research based on secondary data and carried out for a ‎period of ten years, from the financial year 2015 to 2024. The analysis reveals that Yes Bank has made ‎a remarkable recovery in deposits, particularly in CASA and retail deposits, retail lending, and ‎profitability. To sustain this turnaround, the bank has to steer its deposit growth and retail deposits, ‎bring down the CD, concentrate on retail and SME lending, and strategically look at the asset ‎liability management to improve the interest income to interest cost ratio. Additionally, the bank ‎should continue to control operating expenses and improve fee-based income to sustain financial ‎stability‎.
Keywords: Acquisition; Advance Growth; Asset Quality; Capital Adequacy Ratio; CD Ratio; Deposit; Earning ‎Ability; Merger; Reconstruction; Strategic Quotient Ratio; Turnaround Strategy‎.